2022
DOI: 10.3390/ijerph191710629
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Environmental Quality: Analysis of Government Expenditure and the Causal Effect

Abstract: Environmental expenditures (EX) are made by the government and industries which are either long-term or short-term investments. The principal target of EX is to eliminate environmental hazards, promote sustainable natural resources, and improve environmental quality (EQ). Thus, this study looks at the impact of economic growth (EG), and government finance expenditure (GEX) on EQ in Northern Africa and Southern Africa (NASA) republics from 2000–2016. The panel quantile regression (PQR) and panel vector autoregr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 76 publications
(120 reference statements)
0
6
1
2
Order By: Relevance
“…Barrell et al (2021) confirmed the problem of deteriorating efficiency of environmental expenditures across the selected EU countries. Donkor et al (2022) found both positive and negative influence of government finance expenditures on environmental quality in different countries.…”
Section: Co 2 Emissionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Barrell et al (2021) confirmed the problem of deteriorating efficiency of environmental expenditures across the selected EU countries. Donkor et al (2022) found both positive and negative influence of government finance expenditures on environmental quality in different countries.…”
Section: Co 2 Emissionsmentioning
confidence: 97%
“…Carbon dioxide emissions per capita (natural log), (excluding LULUCF * , tonnes of CO 2 equivalent) OECD This is a variable applied as a proxy for environmental degradation (Hatmanu et al, 2022). Scholars examined the ties between government expenditures on environmental protection and environmental quality (emissions of pollutants) (Barrell et al, 2021;Halkos & Paizanos, 2014;Donkor et al, 2022;Wójtowicz et al, 2022). Barrell et al (2021) confirmed the problem of deteriorating efficiency of environmental expenditures across the selected EU countries.…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…However, the agent computing outcome revealed a positive effect of government outlay on development indicators. However, Donkor et al (2022) employed the panel quantile regression and panel VAR techniques in submitting that government spending has a positive and substantial impact on ecological sustainability in northern and southern African countries Yameogo et al (2021) expressed with the GMM estimator that no significant effect existed between globalisation and ecological sustainability for 20 sub-Saharan Africa (SSA) countries. A mixed impact of globalisation on environmental sustainability was found by Leal and Marques (2021).…”
Section: Government Outlay and Sd Nexusmentioning
confidence: 99%
“…This problem is always at the heart of the debates. It is a result of many factors such as the economic sector development, social factors, and energy use [7][8][9].…”
Section: Introductionmentioning
confidence: 99%